PENETRATING THE GLOBAL MARKET: EMPOWERING SALAK COMMODITY MSMES THROUGH STRENGTHENING REGULATION AND BUSINESS OPERATIONAL EFFICIENCY - Sri Sulistyawati; Robert Tua Siregar; Sofiyan; Masdalena; Togar Timoteus Gultom; Iwan Setyawan (RADJA PUBLIKA, 2026)
Training to strengthen regulatory understanding and empowerment for MSME actors is a strategic effort to improve competence in the use of digital technology to strengthen and develop businesses. The activity, which lasted for three days, starting from Sunday, June 14, 2026 to Tuesday, June 16, 2026, aimed to equip participants with practical skills in the fields of regulation, planning management, financial management, food processing, hygiene and sanitation and operational efficiency. The material includes an understanding of regulations, business systems, healthy hygiene processing of products and export-scale business techniques according to market trends, so that it is expected to be able to increase the competitiveness, effectiveness, and sustainability of MSMEs in the midst of the challenges of globalization and digital transformation.